Anticoccidial activity of Artemisia vestita (Anthemideae, Asteraceae) - a traditional herb growing in the Western Himalayas, Kashmir, India. (March 2017) - Ahad, Shazia; Tanveer, Syed; Nawchoo, Irshad Ahmad; Malik, Tauseef Ahmad
Abstract: Coccidiosis, caused by various species of genus Eimeria, is a major parasitic disease in chicken. The increasing resistance of these parasites to currently used anticoccidial drugs has stimulated the search for new methods of control. As part of this effort, a study was designed to see the anticoccidial effect of different solvent extracts of Artemisia vestita- a traditional herb growing in Kashmir Himalayas. The plant extracts were prepared using different solvents. Preliminary toxicity study was first carried out to see the safety of crude plant extracts. A high dose of crude extracts (300 mg/kg body weight) was tested for possession of anticoccidial activity against experimentally induced coccidial infection in broiler chicken. Activity was measured in comparison to the reference drug amprolium on the basis of oocyst output reduction, mean weight gain of birds and feed conversion ratio. Oocyst output was measured using Mc-Masters counting technique. Preliminary toxicity study showed that crude extracts of A. vestita are safe up to dosage of 2000 mg/kg body weight. LD 50 was not determined as mortalities were not recorded in any of the five groups of chicken. For anticoccidial activity crude methanolic extract (CME) of A. vestita showed the maximum effect as evident by oocyst output reduction (71.5 ± 12.2), weight gain of birds (1406.4 ± 12.2) and feed conversion ratio (1.58 ± 0.06), thereby affirming the presence of alcohol soluble active ingredients in the plant. We also tested different doses (100–400 mg/kg body weight) of the CME of A. vestita, the most active extract on E. tenella and observed a dose dependent effect. From the present study it can be concluded that alcoholic extract of A. vestita has the immense potential to contribute to the control of coccidian parasites of chicken. Our results corroborate the use of genus Artemisia and could justify its use in folk medicine for treatment of parasitic diseases. Graphical abstract: Highlights: Artemisia vestita- a traditional herb was tested for controlling Eimeria tenella, a cecal coccidian parasite. Preliminary toxicity study showed that the crude extracts of A. vestita are safe up to dosage of 2000 mg/kg body weight. Crude methanolic extract of A. vestita showed immense potential in controlling coccidian parasites of chicken.